Consumer Attitude and Behavior towards Bio-products in Slovak Republic - Chovancova, Jana; Huttmanová, Emília (Journal of Economic Development, Environment and People, 2014)
Bio-product market is very challenging and developing rapidly. Consumers have raised great interest in healthy and tasty diet with high nutritional compounds, confidence in food safety, environmental and animal welfare concern and also sustainability. The aim of this paper is to analyze consumer attitude and behavior as well as the factors influencing purchasing behavior when deciding to buy bio-products or their substitutes. The essential part of the article presents the partial results of the research, which was directed to consumers buying bio-products in Slovakia.